Money laundering prevention : deterring, detecting, and resolving financial fraud - Turner, Jonathan E. (N.J. : Wiley, 2011)
"A how-to guide for the discovery and prevention of the illegal transfer of money Written for the private sector--where most money laundering takes place--this book clearly explains shows business professionals how to deter, detect, and resolve financial fraud cases internally. It expertly provides an understanding of the mechanisms, tools to detect issues, and action lists to recover hidden funds. Provides action-oriented material that will show how to deter, detect, and resolve financial fraud cases Offers an understanding of the mechanisms, tools to detect issues, and action list to recover hidden funds Covers mechanisms for moving money, identifying risk exposures, and investigating money movement Arming auditors, investigators, and compliance personnel with the guidance that, up until now, has been restricted to criminal investigators, Money Laundering Prevention provides nuts-and-bolts information needed to fully understand the money laundering process"--
Machine generated contents note: ch. 1 Understanding the Process of Money Laundering -- What Is Money Laundering? -- Money Laundering Defined -- Why Do People Launder Money? -- The Money Laundering Cycle -- Money Laundering Is a Criminal Business -- Money Laundering Is Global -- Money Launderers Adapt Technology -- The Role of Technology -- The Role of Banks -- The Role of Nations -- Regional Hotspots -- The Birth of the Financial Action Task Force (FATF) -- Conclusion -- ch. 2 Motivations for Getting Involved -- Involvement Is Personal -- People Weigh the Odds of Success -- Where Do Laundered Funds Come From? -- The Impact of Corruption -- Why Is Corruption Increasing? -- Corruption Always Begins Small -- Bribery and Corruption of Your Employees -- Bribery and Corruption by Your Employees -- Evolution of Government Attitudes -- Official Corruption Impacts Individual Corruption -- Tax Evasion as a Gateway to Money Laundering -- Moving from Taxes to Criminal Activity -- The Rise of Regional and Multinational AML Organizations -- The Connection between Fraud and Money Laundering -- Money Laundering as a Do-It-Yourself Activity -- The Service Providers: Bankers, Accountants, and Lawyers -- Conclusion -- ch. 3 Mechanisms for Moving Money -- Money Laundering Requires Movement through the System -- Broken Windows Encourage Other Crimes -- Look Local, Think Global -- Expanding International Requirements -- Financial Havens Are Expanding -- Money Laundering Is a Growth Industry -- Law Enforcement Gets a Big Boost -- Profit Drives Criminal Activity -- Structuring the Scheme to Succeed -- Why Use a Bank, When You Can Own One? -- Learning from the Big Fraud Schemes -- Confronting the Inevitable -- Balancing Security and Cost -- Effective Fraud Prevention Strategies -- The Fraud Triangle -- Where to Start -- Mitigating Improper Behavior -- Conclusion -- ch. 4 Going Global -- Taking Money around the World -- Moving the Money Offshore -- Avoiding Detection -- Historical Basis for Money Laundering -- Role of Private Banking -- Enhanced Regulations -- The Black Market Peso Exchange -- Increasing Cooperation in Regulation -- Regional Distinctions -- Global Efforts -- The Law Enforcement Focus -- Conclusion -- ch. 5 Technology and Tomorrow -- The Impact of Technology -- The Next Phase of Money Laundering -- Everything Old Becomes New Again -- Being Anybody You Want to Be -- Welcome to the Future -- So What Is the AML Response? -- Evolution of AML Controls -- Adjusting to Rapidly Increasing Scale -- A Highly Flexible Methodology Results in Processes that Are Difficult to Stop -- AML Is a Process, Not a Destination -- All Countries' Regulatory Programs Are Not Equal -- Technology and Offshore Havens Intersect -- The Cost vs. the Benefit -- Consider the Pace of Change and Progress -- Conclusion -- ch. 6 Discovery and Prevention -- Early Warning Is Essential to AML -- Proactive Means Active -- By the Numbers -- Paradigm Shift -- Testing Your Own AML Systems -- Expanding the Business Comparison -- The Regulatory Framework -- High-Risk Areas -- Money Laundering Meets Terror Financing -- Hiding in Plain Sight -- Criminalizing the Concealment Activities -- Creating Financial Fronts -- Keeping the Money Moving -- Keeping the Tax Man Happy -- Conclusion -- ch. 7 Terror Financing -- Terrorists Use Money Laundering Techniques -- Similarities and Distinctions -- Application of the Methodology to Terror Financing -- Global Impact of Financial Crimes -- Alternative Laundering Mechanisms -- Regulatory Responses -- Conclusion -- ch. 8 Identifying Risk Exposures -- AML Exposures: Assessing Financial Institution Risk -- Language, Culture, and Ethnicity -- The Legal Landscape -- Geography: Distance Matters -- The Goal of the Launderer Is to Hide -- The United States Takes a Different Approach -- Laundering Groups Seek to Evade Detection -- A Fractured Enforcement and Regulatory Picture -- The Regulatory Position on Cyber Risks -- Simple Fraud, Still Successful -- Conclusion -- ch. 9 Investigating Money Movement -- Money Laundering Is Now Transnational Organized Crime -- Succeeding in the Investigative Process -- Government Access to Information -- Mining Data for Money Laundering -- Some Products Help the Perpetrators -- Investigating Virtual Payment Technologies -- Looking to the Future Investigative Issues -- Putting an Investigative Plan in Motion -- People Are Essential to Proof -- Finding Money Laundering Abroad -- Money Laundering Exposure during the Financial Industry Consolidation -- Conclusion -- ch. 10 Reporting and Recovery -- Reporting to Law Enforcement -- Honest People Act Differently -- Anticipating Challenges with Cyber Recoveries -- Building Appropriate Controls into Online Payment Systems -- Global Coordination on Future Issues -- Weighing Access vs. Privacy -- Compliance Issues -- Putting Recovery Plans into Action -- Conclusion -- ch. 11 Conclusion.
Includes index.
Keywords: Money laundering -- Prevention